Nanostructured conducting polymer based reagentless capacitive immunosensor - Bandodkar A.J.; Dhand C.; Arya S.K.; Pandey M.K.; Malhotra B.D. (My University, 2025)
Nanostructured polyaniline (PANI) film electrophoretically fabricated onto indium-tin-oxide (ITO) coated glass plate has been utilized for development of an immunosensor based on capacitance change of a parallel plate capacitor (PPC) by covalently immobilizing anti-human IgG (Anti-HIgG) using N-ethyl-N'-(3- dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide chemistry. These fabricated PANI/ITO and Anti-HIgG/PANI/ITO plates have been characterized using scanning electron microscopy, cyclic voltammetry, differential pulse voltammetry and Fourier transform infra-red studies. The capacitance measurements indicate that dielectric medium of this biologically modified PPC (Anti-HIgG/PANI/ITO) is sensitive to HIgG in 5-5×105 ng mL-1 range and has lower detection limit of 1.87 ng mL-1. The observed results reveal that this Anti- HIgG modified PPC can be used as a robust, easy-to-use, reagentless, sensitive and selective immunosensor for estimation of human IgG. © 2009. Springer Science + Business Media, LLC.